Comparative lipidomics analysis of in vitro lipid digestion of sheep milk: Influence of homogenization and heat treatment - Pan Z; Ye A; Fraser K; Li S; Dave A; Singh H (Elsevier Inc on behalf of the American Dairy Science Association, 2024)
This study investigated the changes in sheep milk lipids during in vitro gastrointestinal digestion in response to heat treatment (75°C/15 s and 95°C/5 min) and homogenization (200/50 bar) using lipidomics. Homogenized and pasteurized sheep milk had higher levels of polar lipids in gastric digesta emptied at 20 min than raw sheep milk. Intense heat treatment of homogenized sheep milk resulted in a reduced level of polar lipids compared with homogenized-pasteurized sheep milk. The release rate of free fatty acids during small intestinal digestion for gastric digesta emptied at 20 min followed the order: raw ≤ pasteurized < homogenized-pasteurized ≤ homogenized-heated sheep milk; the rate for gastric digesta emptied at 180 min showed a reverse order. No differences in the lipolysis degree were observed among differently processed sheep milks. These results indicated that processing treatments affect the lipid composition of digesta and the lipolysis rate but not the lipolysis degree during small intestinal digestion.
Keywords: fat globules; fatty acids; lipid composition; lipidome; lipolysis; Animals; Sheep; Milk; Hot Temperature; Lipidomics; Digestion; Fatty Acids, Nonesterified